2021
DOI: 10.1364/oe.419877
|View full text |Cite
|
Sign up to set email alerts
|

848 ppi high-brightness active-matrix micro-LED micro-display using GaN-on-Si epi-wafers towards mass production

Abstract: In this paper, fabrication processes of a 0.55-inch 400 × 240 high-brightness active-matrix micro-light-emitting diode (LED) display using GaN-on-Si epi-wafers are described. The micro-LED array, featuring a pixel size of 20 µm × 20 µm and a pixel density of 848 pixels per inch (ppi), was fabricated and integrated with a custom-designed CMOS driver through Au-Sn flip-chip bonding. Si growth substrate was removed using a crack-free wet etching method. Four-bit grayscale images and videos are clearly rendered. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…For micro-LEDs, the situation is more complicated because the EQE depends on the chip size. Based on previous studies [130][131][132][133] , we separately calculate the luminous efficacy for RGB micro-LEDs with chip size ≈ 20 µm. For the scheme of direct combination of RGB micro-LEDs, the luminous efficacy is around 5 lm/ W. For QD-conversion with blue micro-LEDs, the luminous efficacy is around 10 lm/W with the assumption of 100% color conversion efficiency, which has been demonstrated using structure engineering 114 .…”
Section: Comparison Of Light Engine Performancementioning
confidence: 99%
“…For micro-LEDs, the situation is more complicated because the EQE depends on the chip size. Based on previous studies [130][131][132][133] , we separately calculate the luminous efficacy for RGB micro-LEDs with chip size ≈ 20 µm. For the scheme of direct combination of RGB micro-LEDs, the luminous efficacy is around 5 lm/ W. For QD-conversion with blue micro-LEDs, the luminous efficacy is around 10 lm/W with the assumption of 100% color conversion efficiency, which has been demonstrated using structure engineering 114 .…”
Section: Comparison Of Light Engine Performancementioning
confidence: 99%
“…2020) [ 33 ]. Qi et al built a micro-LEDs array on a 0.55-in (400 × 240) gallium nitride substrate with a pixel density of 848 PPI and full width at half maximum (FWHM) of 18.2 nm to produce a high-brightness, high-resolution micro-LEDs display [ 34 ]. The aforementioned findings indicate that combining blue micro-LEDs with QDs is currently the best solution for achieving full color.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with self-power-consuming OLED technology, the LCD technology is superior in terms of lifetime, cost, resolution and peak brightness 6 . Many technology giants are employing cost-effective LCDs for AR dis-plays.…”
Section: Introductionmentioning
confidence: 99%
“…At 2017 SID display Week, Samsung launched a 1.96-inch ultra-high definition (UHD) display for HM-Ds, with an amazing pixel density of 2250 PPI, and BOE exhibited a retina VR display (2300 PPI) with a size of 5.3 cm. Although the LCD technology has the advantages as mentioned above, its response time is about 100 times larger than that of the OLED technology 6 , as listed in Table 1. To solve the problem of long response time in traditional LCD, Gou et al reported a fire-new mode, including a hole-type vertical alignment-fringe field switching (VA-FFS) technique, which optimized liquid crystal materials by electrodynamic optimization 4 .…”
Section: Introductionmentioning
confidence: 99%